Cycloaddition reactions of nitrosoalkenes, azoalkenes and nitrile oxides mediated by hydrotalcite - Lemos, A. (2012)
Mg:Al 3:1 hydrotalcite (Ht), used in catalytic quantities, promotes the generation of nitrosoalkenes, azoalkenes and nitrile oxides. These can be intercepted in situ by heterocycles and olefins in [4+2] and [3+2] cycloaddition reactions, producing dihydro-1,2-oxazines, tetrahydropyridazines and isoxazolines. The regeneration and reuse of Ht without loss of activity and the absence of organic solvent are the main advantages of this methodology.